TINGKAT KESEJAHTERAAN PEDAGANG PAKAIAN BEKAS IMPORT DI PASAR TERONG KELURAHAN TOMPO BALANG KECAMATAN BONTOALA KOTA MAKASSAR - Affan, Trisna Andi; Leo, M. Nur Zakariah (Jurnal Environmental Science, 2019)
This study aims to: 1) find out what factors influence the welfare level of traders choosing to work as imported used clothing traders in the eggplant market. 2) To find out the level of welfare of imported used clothing traders in the eggplant market. This type of research is quantitative descriptive research. The population in this study were all imported used clothing traders, namely 321 people. Data collection techniques are determined through observation, interview, and documentation techniques. The results showed that clothing traders were generally productive aged 16-60 years with 219 men and 102 women. The average level of education for imported used clothing traders was graduating junior high, high school and undergraduate. With the economic income, imported used clothing traders generally make a monthly payment of Rp.4,000,000 - Rp.5,000,000. with the average welfare level is medium.